2016
DOI: 10.1007/s10815-016-0750-0
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in preimplantation genetic diagnosis and screening

Abstract: Preimplantation genetic diagnosis/screening (PGD/PGS) aims to help couples lower the risks of transmitting genetic defects to their offspring, implantation failure, and/or miscarriage during in vitro fertilization (IVF) cycles. However, it is still being debated with regard to the practicality and diagnostic accuracy of PGD/PGS due to the concern of invasive biopsy and the potential mosaicism of embryos. Recently, several non-invasive and high-throughput assays have been developed to help overcome the challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 90 publications
1
29
0
1
Order By: Relevance
“…Similar to blastocoel fluid, embryo culture medium was suggested to harbour DNA that can be used for further analysis (Palini et al, 2013;Scaruffi et al, 2011). Therefore, the possibility of non-invasive preimplantation genetic screening (PGS) was discussed as a potential future technique for embryo assessment (Cohen et al, 2013;Hammond et al, 2016;Lu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to blastocoel fluid, embryo culture medium was suggested to harbour DNA that can be used for further analysis (Palini et al, 2013;Scaruffi et al, 2011). Therefore, the possibility of non-invasive preimplantation genetic screening (PGS) was discussed as a potential future technique for embryo assessment (Cohen et al, 2013;Hammond et al, 2016;Lu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In Spain, where the number of PGD/PGS cycles has tripled between 2010 and 2016, more than 80% of these cycles were referred to PGS (SEF, 2010;SEF, 2016). Furthermore, biopsies extracted for PGS will increasingly be used also for PGD, which will enable detecting a wider variety of disorders; multifactorial, of later-onset, lower level of penetrance and even less severe expressions, providing higher accuracy and success rates (Lu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Biopsies can also be used for PGS, a global quantitative analysis of the entire genome which serves to detect and transfer only euploid embryos (i.e., without chromosomal structure anomalies). This procedure assumes that an euploid embryo has better chances to develop into a fetus and a healthy baby (Lu et al, 2016;Casper et al, 2017). PGD cycles represent a minor share of all IVF cycles, while PGS is more commonly used and mainly offered to patients of advanced age whose eggs tend to have higher levels of aneuploidy.…”
Section: Technical Factorsmentioning
confidence: 99%
“…Studies within other settings have found that it is possible to obtain BF-DNA, using RT-PCR to analyze several targeted genes (GADPH, TSPY1, and TBC1D3) A whole-genome microarray was also attempted on five amplified DNA products obtained from the BF, but found a karyotype in only two samples [10]. Polisseni et al reported on the use of DNA fingerprinting for eight chromosomes from 11 paired BF-DNA samples separated from whole embryo DNA [11].…”
Section: Discussionmentioning
confidence: 99%